A Study of Placemaking for Urban Sustainability - Wardhani, Dhiyan Krishna; Wastunimpuna, Benediktus Yosef Arya (Talenta Publisher, 2025)
Urbanization presents challenges such as sustainability and urban development including social equity, environmental degradation, declining community engagement, and livability. Placemaking has developed as an effective approach to enhance the quality of public spaces by making them more inclusive, usable and relevant to the community. This study investigates how placemaking promotes urban sustainability by discussing its core principles, approaches, and results. Using a descriptive exploratory research design, the study conducts a thematic literature review of key publications from 2010 - 2024, focusing on placemaking principles, strategies, and outcomes. The key findings indicate that while placemaking fosters social cohesion, local identity, and ecological adaptation, its success in inclusive participation and community relationship. The study identifies strategic, creative, and tactical placemaking as critical frameworks with effectiveness that contributes to the disclosure of future urban development toward resilient, vibrant, culturally rich urban systems.